2021
DOI: 10.1111/cts.13194
|View full text |Cite
|
Sign up to set email alerts
|

Exploration for the effect of renal function and renal replacement therapy on pharmacokinetics of remdesivir and GS‐441524 in patients with COVID‐19: A limited case series

Abstract: Remdesivir, an antiviral agent for the treatment of coronavirus disease 2019 (COVID‐19), is metabolized intracellularly, with these metabolites eliminated predominantly in urine. Because of a lack of safety and pharmacokinetic (PK) data, remdesivir is not currently recommended for patients with estimated glomerular filtration rate less than 30 ml/min/1.73 m 2 and those on hemodialysis. This study evaluated the PKs of remdesivir and its metabolite, GS‐441524, in patients with COVID‐19 who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…GS-441524 clearance was found to be dependent on the eGFR, which confirms the observations by Choe et al and Sukeishi et al ( 20 , 21 ). Our simulations show that accumulation as a result of reduced GS-441524 clearance leads to markedly higher GS-441524 concentrations in COVID-19 patients with severely reduced renal function.…”
Section: Discussionsupporting
confidence: 90%
“…GS-441524 clearance was found to be dependent on the eGFR, which confirms the observations by Choe et al and Sukeishi et al ( 20 , 21 ). Our simulations show that accumulation as a result of reduced GS-441524 clearance leads to markedly higher GS-441524 concentrations in COVID-19 patients with severely reduced renal function.…”
Section: Discussionsupporting
confidence: 90%
“…The PK of remdesivir in COVID‐19 is poorly understood despite the clinical need for remdesivir. Real‐world clinical studies have evaluated the PK of remdesivir and GS‐441524 in patients with COVID‐19 10–12,15,16 . A few real‐world PK studies on remdesivir, including two PopPK analyses, 11,12 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Real‐world clinical studies have evaluated the PK of remdesivir and GS‐441524 in patients with COVID‐19. 10 , 11 , 12 , 15 , 16 A few real‐world PK studies on remdesivir, including two PopPK analyses, 11 , 12 have been reported. Briefly, these studies characterized the rapid elimination of remdesivir and relatively slow elimination of GS‐441524.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the unlicensed status, adequate variables for evaluating drug safety of GS‐441524 have not been established in cats. In human patients, remdesivir and its metabolite GS‐441524 are recommended to be used with caution in patients with impaired renal function 12 . With no previous reports of this complication in cats receiving GS‐441524, it is possible that predisposing factors (including renal dysfunction) may make some cats more likely than others to form these medication‐based uroliths 2‐4 .…”
Section: Discussionmentioning
confidence: 99%